Активність калікреїну в плазмі крові і тканині міокарда щурів із стрептозотоциновим цукровим діабетом - Yefimov, A.S.; Gonchar, I.V.; Kovzun, E.I. (Ендокринологія | Endokrynologia, 2020)
Активність калікреїну в плазмі крові і тканині міокарда щурів із стрептозотоциновим цукровим діабетом